2016
DOI: 10.1177/1359105315622557
|View full text |Cite
|
Sign up to set email alerts
|

Type D personality and physical inactivity: The mediating effects of low self-efficacy

Abstract: Type D personality is associated with health-damaging behaviours among the general population. This study assessed the relationship between Type D personality, physical activity and self-efficacy. A total of 189 participants completed measures of Type D personality, physical activity and self-efficacy. Type D individuals had significantly lower levels of self-efficacy and engaged in significantly less walking and total exercise compared to non-Type D's. Furthermore, self-efficacy fully mediated the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 41 publications
3
19
0
Order By: Relevance
“…Therefore, it is likely that the feelings of NA cause such individuals to believe that they lack the confidence, strength, or patience to take control of their diabetic condition and implement appropriate care, and, as a result, they would score lower in self-efficacy. More recent studies revealed that self-efficacy mediated the relationship between Type D personality and physical activity,36 and the relationship between Type D and medication adherence 37. Our findings are consistent with these previous studies and highlight the negative impact of Type D personality on patient self-efficacy in controlling their medical conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it is likely that the feelings of NA cause such individuals to believe that they lack the confidence, strength, or patience to take control of their diabetic condition and implement appropriate care, and, as a result, they would score lower in self-efficacy. More recent studies revealed that self-efficacy mediated the relationship between Type D personality and physical activity,36 and the relationship between Type D and medication adherence 37. Our findings are consistent with these previous studies and highlight the negative impact of Type D personality on patient self-efficacy in controlling their medical conditions.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, poorer performance was associated with lower self-confidence prior to the task and increased use of resignation/withdrawal coping after completion of the task. This is supported by findings that Type D individuals have a tendency to search the environment for trouble [ 65 ] and report lower levels of general self-efficacy [ 37 ]. The lower levels of self-efficacy in the study by Wiencierz and Williams [ 37 ] were associated with significant less total exercise participation and walking in Type D versus non Type D individuals.…”
Section: Studymentioning
confidence: 69%
“…In healthy, young [ 24 ], and older [ 32 ] samples as well as in patients with diabetes [ 33 ], research findings consistently relate Type D personality to less healthy eating behaviors. Also, across healthy and patient samples, Type D personality was associated with less regular physical exercise [ 23 , 32 34 ]. Also in cardiac patients, the relationship between lack of exercise and Type D personality is evident, with Type D patients exercising less and feeling less motivated to exercise [ 23 ].…”
Section: Behavioral Risk Pathwaysmentioning
confidence: 99%